Influence of Label and Solid Support on the Performance of Heterogeneous Immunoassays - Makhneva, Ekaterina; Sklenárová, Dorota; Brandmeier, Julian C; Hlaváček, Antonín; Gorris, Hans H; Skládal, Petr; Farka, Zdeněk (Analytical chemistry, 2022)
Conventional immunochemical methods used in clinical analysis are often not sensitive enough for early-stage diagnosis, resulting in the need for novel assay formats. Here, we provide a detailed comparison of the effect of different labels and solid supports on the performance of heterogeneous immunoassays. When comparing three types of streptavidin-modified labels─horseradish peroxidase, carboxyfluorescein, and photon-upconversion nanoparticles (UCNPs)─UCNPs led to the most sensitive and robust detection of the cancer biomarker prostate-specific antigen. Additionally, we compared the immunoassay formats based on conventional microtiter plates and magnetic microbeads (MBs). In both cases, the highest signal-to-background ratios and the lowest limits of detection (LODs) were obtained by using the UCNP labels. The MB-based upconversion-linked immunosorbent assay carried out with a preconcentration step provided the lowest LOD of 0.46 pg/mL in serum. The results demonstrate that the use of UCNPs and MBs can significantly improve the sensitivity and working range of heterogeneous immunoassays for biomarker detection.
Keywords: Limit of Detection; limita detekce; magnetismus; Nanoparticles; Immunosorbents; Humans; imunosorbenty; Magnetics; mužské pohlaví; streptavidin; lidé; imunoanalýza; Male; Immunoassay; Streptavidin; nanočástice